Optimization of the consumption function under the North American Free Trade Agreement: Consumption function - Ledesma, Dora; Hernández-Hernández, Lidia; Muciño-Porras, María Teresa Leonor (Archives of Business Research, 2021)
In the last 40 years, the country has turned to developing the primary and tertiary sectors with a tax policy heavily taxing goods outside the basic basket and generalizing others. On the other hand, Government implemented support programs for vulnerable sectors. The imbalance between what the government receives and grants created greater poverty, affecting mainly households in the first three income deciles. This work shows this imbalance in different scenarios using an optimization model.